HUBUNGAN KORELATIF HUKUM DAN MASYARAKAT DITINJAU DARI PERSPEKTIF SOSIOLOGI HUKUM - Roseffendi Roseffendi (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: Legal causes are not relevant to the reality of society because the existing law is formed in a top-down manner, which comes from the will of the elite (the ruler), while the community is the target object. Even though the law can be responsive, the law must be formed in a bottom-up manner from the reality that lives in the community. The results of the study can be concluded that the usefulness of the sociological perspective in analyzing legal issues (legal sociology) is, among others: Legal sociology is useful for providing capabilities for understanding the law in a social context, Mastery of sociological concepts of law can provide capabilities to conduct analysis of the effectiveness of law in society, both as a means of social control, a means to change society and a means to regulate social interactions, to achieve certain social conditions, and legal sociology provide possibilities and the ability to evaluate the effectiveness of law in society . Keywords: Law, Society, Sociology of Law